The marketization of care: Global challenges and national responses in Australia. (July 2018) - Fine, Michael; Davidson, Bob
Care is a social necessity for life. Ensuring access to appropriate care at crucial points in the life course became a political necessity soon after the mid-20th century, as the right to suitable care became recognized as a fundamental entitlement of citizenship in most advanced capitalist economies. Over recent decades there has been a shift away from more traditional welfare state forms of public services towards increasingly marketized systems of provision. Changes in the provision of care in the public domain are associated with an increasing reliance on private capital and competition between a variety of providers, with public agencies competing alongside private for-profit and not-for-profit agencies. Drawing on care theory, historical sociology and political economic analysis, this article examines the conflicting tensions that shape aged care under marketization. Using Australia as a case study, it is argued that as private capital and resources take the place of scarce public resources and enable expenditure cuts to be presented as innovation, better services and more 'consumer choice', it is not the market but the finance, regulation and management work of the state that is the essential determinant of the assistance previously provided through non-market processes.